2015
DOI: 10.4236/ajac.2015.61005
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Removal and Reduction of Cr(VI) by Wool: Short and Long Term Equilibration Studies

Abstract: Hexavalent chromium removal from wastewater using sheep wool was investigated at several equilibration periods. The influence of contact time, pH, adsorbent dosage and initial concentration was investigated. Adsorption isotherms for long and short periods were fitted to the Langmuir and Freundlich isotherms. For short contact times, the Langmuir adsorption isotherm was obeyed with no detectable change in the oxidation state but removal percentages did not exceed 90%. Long contact times resulted in more than 99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 24 publications
1
25
0
1
Order By: Relevance
“…Peaks at 2400 cm −1 , 1666 cm −1 , 1634 cm −1 and 1588 cm −1 are characteristic of anthraquinone molecules, whereas those at 1155 cm −1 and 728 cm −1 are for sulfonate groups. Figure 7b shows spectra of free wool with features described earlier [31]. Upon complexation with ARS, changes were observed (Figure 7c).…”
Section: Ftir Spectrasupporting
confidence: 53%
See 2 more Smart Citations
“…Peaks at 2400 cm −1 , 1666 cm −1 , 1634 cm −1 and 1588 cm −1 are characteristic of anthraquinone molecules, whereas those at 1155 cm −1 and 728 cm −1 are for sulfonate groups. Figure 7b shows spectra of free wool with features described earlier [31]. Upon complexation with ARS, changes were observed (Figure 7c).…”
Section: Ftir Spectrasupporting
confidence: 53%
“…The highest removal of Cr(VI) was 93%, as detected by AAS. However, previous studies by our group revealed that, at this short term contact, slight amounts of Cr(III) were released into solution [31]. This process causes incomplete removal of Cr(VI).…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…Достаточно назвать ряд книг и сборников статей [1][2][3][4][5][6][7][8][9][10][11][12], обзоров , посвященных в целом проблеме веще-ственного анализа, а также вопросам определения химических форм ртути [36,37], таллия [38], олова [39], мышьяка [40,41], сурьмы [42,43], хрома [44,45], се-лена [46], железа [47] в разных объектах (преимущественно экологических и био-медицинских) разнообразными методами и их сочетаниями. Справедливости ради надо отметить, что и в русскоязычной химико-аналитической периодике опубли-ковано несколько обстоятельных и фундаментальных книг и обзорных статей по вопросам вещественного (фазового, рационального) анализа [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64].…”
unclassified
“…Column filtration and batch equilibrium by low cost adsorbents are the most common methods used in removing Pb(II) and other toxic heavy metals from wastewaters. UAE sands were shown to be efficient adsorbents for the removal and recovery of Pb(II) and other heavy metals from aqueous solutions [1] [2], and for the removal and speciation of Cr(III) and Cr(VI) [3] [4]. Reports on heavy metal removal from solutions by sawdust [5], eggshell [6], bentonite, molasses and fly ash [7] have also included X-ray fluorescence (XRF) data on these adsorbents.…”
Section: Introductionmentioning
confidence: 99%